Odnos med depresivnostjo, naučeno nemočjo, spolom in šolskim uspehom pri mladostnicah in mladostnikih - Jehart, Daša (Psihološka obzorja (Ljubljana), 2023)
In this study we investigated the relationship between learned helplessness, depressiveness, gender, and academic achievement in adolescents. We also investigated which school subjects induce the highest levels of helplessness. Coping Competence Questionnaire (CCQ) and The Center for Epidemiologic Studies Depression Scale (CESD) were administered to a sample of 297 students, aged between 16 and 18 years. We also designed a short questionnaire for their teachers with which we obtained data on perceived learned helplessness and the frequency of occurrence of such behavior in each adolescent individually. The results showed a significant positive relationship between depressiveness and learned helplessness. We observed that girls suffered more frequently from depressive symptoms and learned helplessness than boys, while adolescents with higher school grades reported less symptoms of depressiveness than academically unsuccessful adolescents. Boys with lower grades experienced helplessness more often than academically more successful boys, while the opposite was true for girls. Adolescents feel the most helpless at the subjects of Slovenian, physics, and mathematics, followed by German, chemistry, biology and English. They feel the least helpless at music, history, sport, art, and geography. Given that adolescents spend a large part of their time in the school environment, it is important to highlight the role of teachers and social workers who should be empowered to identify and attempt to prevent the development of depressive symptoms and learned helplessness in their students.
Keywords: academic achievement; adolescents; depresivnost; depression; gender differences; learned helplessness; mladostniki; naučena nemoč; razlike med spoloma; učna uspešnost